How accurate is the CAPM approach compared to the Reward Beta for shares of manufacturing and mining companies in Indonesia's LQ45 Index? - Handri Handri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study evaluates the efficacy of the Capital Asset Pricing Model (CAPM) and Beta Reward Model in forecasting stock returns of companies within the manufacturing and mining sectors listed on Indonesia's LQ45 index. Utilizing monthly closing stock prices from January 2010 to December 2019, the research focuses on ten companies—five from each sector—that consistently appeared in the index throughout the study period. The analysis involves a classic assumption test followed by regression analysis for each company. Key performance indicators, including R-squared, Root Mean Square Error (RMSE), and Mean Absolute Error (MAE), are employed to compare the predictive capabilities of the CAPM and Beta Reward Model. The findings indicate a systematic and superior performance of the Beta Reward Model over the CAPM in predicting stock returns in the Indonesian context. This study contributes to the existing literature on stock return prediction models and provides practical insights for investors and financial analysts in Indonesia.